Peran Pernyataan Orientasi Tujuan Kinerja dan Pernyataan Orientasi Tujuan Pembelajaran terhadap Kemampuan Mahasiswa - Ahmad Muzaki; Dyah Probowulan; Achmad Syahfrudin (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
Objective orientation is a mental framework as individuals give an impression and respond to situations or events that they face. Typically there are two kinds of goal orientation, namely orientation of performance goals (performance orientation) and orientation of learning goals (learning goal orientation). The phenomenon that there are still students who are extension or extension of time in doing the Final Project are all caused by the ability possessed by the individual. There are three factors that underlie the ability; self-efficacy, goals and performance. The researcher followed up the existence problems in the 2015 Accounting Study Program with four samples of Higher Education in Jember Regency, there were 82 respondents to answer the questionnaire given. Therefore an analytical tool is needed to determine the abilities possessed by students of the Accounting Study Program in Jember Regency. In this study researchers will test performance goal orientation statements (state performance goal orientation) and statement of learning goal orientation (state learning goal orientation) on self-efficacy (self-efficacy), goals (goals) and performance (performance) that each individual has. Keywords: Goal Orientation, State Goal Orientation Learning, State Performance Goal Orientation, Self-Efficacy, Goals and Performance.